Diagnostic Accuracy of Cytological Sampling Techniques by Bronchoscopy in the Diagnosis of Lung Cancer - Agarwal, Saumya; Gupta, Mamta (Annals of Pathology and Laboratory Medicine, 2018)
Background: With advent of newer diagnostic modalities for obtaining small biopsies and cytologic samples by bronchoscopy it is important to assess the diagnostic accuracy of these techniques. Material and Methods: A Retrospective and Prospective study was conducted on 347 bronchoscopic specimens from 200 patients with clinical and / or radiological suspicion of carcinoma lung. To evaluate the role and relative diagnostic accuracies of bronchial washings, brushings and broncho-alveolar lavage in the diagnosis of lung cancer Results : 119/200 cases were diagnosed as positive for malignancy on cytology and 56/80 cases were confirmed positive on histopathological evaluation. Cytological materials included in the study were, 8 BW, 180 BAL and 159 BB constituting a total sample size of 347. The overall sensitivity of BW, BAL and BB was 25%, 72% and 94% respectively. Thus, BB provided a significantly superior sensitivity and improved the diagnostic yield. Squamous cell carcinoma was the most common histologic type of malignancy diagnosed on both cytology and histopathologic evaluation with accuracy of 78.8%. A specific diagnosis of malignancy was made in 124 cases (62%) by combination of cytology and biopsy. Conclusion : Cytologic samples and small biopsies obtained under bronchoscopic guidance are forming important samples for diagnosing and classifying lung tumours. Every technique has utility and limitation. However, combination of different methodologies on bronchoscopy increases the diagnostic accuracy.